Safety attitudes culture remain stable in a transplant center: evidence from the coronavirus pandemic - Zhang, Chi; Wilson-Sheehan, Sena; Ruch, Brianna; Wagler, Josiah; Abidali, Ali; Lim, Elisabeth S.; Chang, Yu-Hui; Fowler, Christopher; Douglas, David D.; Mathur, Amit K. (Frontiers in Transplantation, 2023)
Background We sought to understand how safety culture may evolve during disruption, by using the COVID-19 pandemic as an example, to identify vulnerabilities in the system that could impact patient outcomes. Methods A cross-sectional analysis of transplant personnel at a high-volume transplant center was conducted using the Safety Attitudes Questionnaire (SAQ). Survey responses were scaled and evaluated pre- and post-COVID-19 (2019 and 2021). Results Two-hundred and thirty-eight responses were collected (134 pre-pandemic and 104 post-pandemic). Represented organ groups included: kidney (N = 89;38%), heart (N = 18;8%), liver (N = 54;23%), multiple (N = 66;28%), and other (N = 10;4%). Responders primarily included nurses (N = 75;34%), administration (N = 50;23%), and physicians (N = 24;11%). Workers had high safety, job satisfaction, stress recognition, and working conditions satisfaction (score >75) both before and after the pandemic with overlapping responses across both timepoints. Stress recognition, safety, and working conditions improved post-COVID-19, but teamwork, job satisfaction, and perceptions of management were somewhat negatively impacted (all p > 0.05). Conclusions Despite the serious health care disruptions induced by the pandemic, high domain ratings were notable and largely maintained in a high-volume transplant center. The SAQ is a valuable tool for healthcare units and can be used in longitudinal assessments of transplant culture of safety as a component of quality assurance and performance improvement initiatives.